Effect of technological camber in the facets of a cellular filler on its physical and mechanical characteristics - Kondratiev, Andrii; Nabokina, Tatiyna (Eastern-European Journal of Enterprise Technologies, 2019)
Among a variety of technological defects of a cellular filler affecting its physical and mechanical characteristics, one of the most essential is believed to be the initial technological camber of facets in its cell. The paper reports a study into the effect of technological camber of a cellular filler's facets on its physical-mechanical characteristics, which ensures the stabilization of its quality and, consequently, the operational characteristics of structures based on it. In contrast to available studies, we have considered a discrete-element cell model. A cellular filler has been represented in the form of a structure consisting of various elements: facets of a single foil, facets of two glued layers of foil, and imaginary edges – the angular butt joint zones of two neighboring facets. The process of consistent loss of bearing ability by the cell elements of a cellular filler under transverse compression and longitudinal shear has been investigated. This analysis of the performance of separate elements of a cell in the presence of the initial technological camber has made it possible to take into consideration the operational patterns of each of them by building the appropriate load-type chart of filler deformation. On this basis, we have devised an approach that makes it possible to predict the character of cellular filler operation taking into consideration the patterns in accepting the loading by separate elements of the honeycomb cell in the presence of the initial technological camber in them. Recommendations have been given for using the obtained results within the approaches, proposed in a series of studies, for optimizing cellular structures for the mass of design parameters. The recommendations enable the synthesis of a module for the verification optimization unit, which produces a conclusion on the carrying capacity of an optimal, in terms of mass, variant of the sandwich-type structure with a cellular filler, taking into consideration the presence in its facets of initial technological camber within the range of regulated tolerance. Such synthesis at the modern level of production technology of a cellular filler would help implement almost exhaustive capabilities of this type of the filler, as well as the structures based on it.